2014
DOI: 10.1074/jbc.m114.554501
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl Activates Janus Kinase 2 in Normal Hematopoietic Cells

Abstract: Background: Jak2 mediates cytokine-stimulated physiological events, but the mechanism of its activation is still unknown. Results: IL-3 stimulated c-Abl kinase activity leading to Jak2 activation through direct interaction with c-Abl. Conclusion: c-Abl activates Jak2 in response to IL-3 in normal hematopoietic cells. Significance: Our findings reveal a novel role of c-Abl kinase in Jak2 activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…We have previously shown that Jak2 kinase activity was required for the stability of Bcr-Abl by phosphorylating Tyr 177 within the Bcr portion of Bcr-Abl [ 41 ], which triggers the binding of Grb2 to pTyr 177 leading Ras pathway members associate with Bcr-Abl [ 42 ]. As Shc is also known to bind to Bcr-Abl, the interaction between Grb2 and Shc also causes Ras pathway members to bind to a second site in Bcr-Abl besides the tyrosine 177 site [ 43 ] Our previous cellular based pull down experiments and the bimolecular fluorescence complementation studies documented that Jak2 directly binds to Bcr-Abl and c-Abl through their C-terminal and kinase domains of c-Abl [ 4 , 44 ]. Bcr-Abl and c-Abl tyrosine kinases specifically phosphorylated Y1007 of Jak2 leading to its kinase activation [ 4 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that Jak2 kinase activity was required for the stability of Bcr-Abl by phosphorylating Tyr 177 within the Bcr portion of Bcr-Abl [ 41 ], which triggers the binding of Grb2 to pTyr 177 leading Ras pathway members associate with Bcr-Abl [ 42 ]. As Shc is also known to bind to Bcr-Abl, the interaction between Grb2 and Shc also causes Ras pathway members to bind to a second site in Bcr-Abl besides the tyrosine 177 site [ 43 ] Our previous cellular based pull down experiments and the bimolecular fluorescence complementation studies documented that Jak2 directly binds to Bcr-Abl and c-Abl through their C-terminal and kinase domains of c-Abl [ 4 , 44 ]. Bcr-Abl and c-Abl tyrosine kinases specifically phosphorylated Y1007 of Jak2 leading to its kinase activation [ 4 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis assay was performed as described previously [ 44 ]. Briefly, cells were seeded in 12 well plate at 0.5×10 6 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…The proliferation of cancer cells is sensitive to HSP90 inhibition using small molecules that target the ATPase activity of the chaperone (Tao et al, 2015;Wang et al, 2013a). HSP90 is likely required for the stabilization of a subset of proteins that is critical for cell proliferation.…”
Section: A Screen To Identify Chromatin Regulators Functionally Intermentioning
confidence: 99%
“…Both are murine-derived cell lines dependent on IL3 for viability and growth and have been extensively used as a model system for studying transforming properties of oncogenes (27)(28)(29)(30)(31). The choice of the 32D cells over Ba/F3 cells was due to their more established origin (32)(33)(34) and availability.…”
Section: Fgfr3-tacc3 Promotes Il3 Independent Cell Growthmentioning
confidence: 99%